WHAT MOST INFLUENCE ON NON-PERFORMING LOAN IN INDONESIAN ISLAMIC COMMERCIAL BANKS? - Lilis Renfiana; Siti Nur Azizah (IQTISHADUNA, 2022)
Problem financing arises because of the customer's failure to fulfill his obligations. So it has an impact on the profitability of the bank. The research objective is to examine factors that affect non-performing loans at Islamic commercial banks. These factors include, operating costs to operating income, interest rates/ BI Rate, Financing to Deposit Ratio, and the inflation. The sample used in this study wasIslamic commercial banks exchange 2011-2020. Data analysis techniques using multiple linear regression. The study results inform an influence between the predictor variables and the response variables based on functions in the model. The variables that affect non-performing loans significantly only Operating Cost to Operating Income (BOPO). And 3 other variables Inflation, BI Rate, FDR have no significant effect on NPF, but simultaneously all dependent variables affect the Independent variable. Therefore banking authorities need to control Operating Cost to Operating Income so as not to disturb the profitability.